Antenatal antioxidant treatment with melatonin to decrease newborn neurodevelopmental deficits and brain injury caused by fetal growth restriction. Issue 3 (22nd February 2014) - Miller, Suzanne L.; Yawno, Tamara; Alers, Nicole O.; Castillo‐Melendez, Margie; Supramaniam, Veena G.; VanZyl, Niel; Sabaretnam, Tharani; Loose, Jan M.; Drummond, Grant R.; Walker, David W.; Jenkin, Graham; Wallace, Euan M.
Abstract Fetal intrauterine growth restriction (IUGR) is a serious pregnancy complication associated with increased rates of perinatal morbidity and mortality, and ultimately with long‐term neurodevelopmental impairments. No intervention currently exists that can improve the structure and function of the IUGR brain before birth. Here, we investigated whether maternal antenatal melatonin administration reduced brain injury in ovine IUGR. IUGR was induced in pregnant sheep at 0.7 gestation and a subset of ewes received melatonin via intravenous infusion until term. IUGR, IUGR + melatonin (IUGR + MLT) and control lambs were born naturally, neonatal behavioral assessment was used to examine neurological function and at 24 hr after birth the brain was collected for the examination of neuropathology. Compared to control lambs, IUGR lambs took significantly longer to achieve normal neonatal lamb behaviors, such as standing and suckling. IUGR brains showed widespread cellular and axonal lipid peroxidation, and white matter hypomyelination and axonal damage. Maternal melatonin administration ameliorated oxidative stress, normalized myelination and rescued axonopathy within IUGR lamb brains, and IUGR + MLT lambs demonstrated significant functional improvements including a reduced time taken to attach to and suckle at the udder after birth. Based on these observations, we began a pilot clinical trial of oral melatonin administration to women with an IUGR fetus. Maternal melatonin was not associated with adverse maternal or fetal effects and it significantly reduced oxidative stress, as evidenced by reduced malondialdehyde levels, in the IUGR + MLT placenta compared to IUGR alone. Melatonin should be considered for antenatal neuroprotective therapy in human IUGR.